2013
DOI: 10.1016/j.ijgo.2013.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction after pregnancy‐induced hypertension

Abstract: Women with a history of PIH were found to have a higher frequency of long-term endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 19 publications
0
36
0
6
Order By: Relevance
“…Women with a history of preeclampsia are at higher risk for developing diabetes mellitus,6 stroke,7 and cardiovascular8 and renal diseases9 in later life. This susceptibility to cardiorenal and metabolic diseases post–index pregnancy has been attributed to the pathophysiological mechanisms10, 11 initiated by the placental ischemia. In addition to the maternal effects, preeclampsia is highly associated with intrauterine growth restriction12 and developmentally programs the increased risk for cardiovascular disease,13, 14 stroke,15 renal disease,16 and metabolic dysfunction17, 18 in the adult offspring of preeclamptic women 19.…”
mentioning
confidence: 99%
“…Women with a history of preeclampsia are at higher risk for developing diabetes mellitus,6 stroke,7 and cardiovascular8 and renal diseases9 in later life. This susceptibility to cardiorenal and metabolic diseases post–index pregnancy has been attributed to the pathophysiological mechanisms10, 11 initiated by the placental ischemia. In addition to the maternal effects, preeclampsia is highly associated with intrauterine growth restriction12 and developmentally programs the increased risk for cardiovascular disease,13, 14 stroke,15 renal disease,16 and metabolic dysfunction17, 18 in the adult offspring of preeclamptic women 19.…”
mentioning
confidence: 99%
“…However, after the AG490 injection, p/t-JAK2, p/t-STAT3 and SOCS1 expressions were downregulated. PIH causes the release of anti-angiogenic factors into the mother's circulation, resulting in endothelial injury [2,3]. Previous studies demonstrated that the combined treatment of anti-placental growth factor (PLGF) and vascular endothelial growth factor A (VEGF-A) could reduce ocular hemangiomas growth and choroidal neovascularization [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, this high-incidence disease of pregnant women can damage the brain, heart, kidney and other human organs [2]. PIH has been correlated with aberrant placentation, which leads to the release of anti-angiogenic factors into the mother's circulation, resulting in endothelial injury as well as maternal and fetal damage [3]. PIH induces a wide variety of disorders, such as gestational hypertension, preeclampsia and eclampsia [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are complications of the fetus and newborn associated with hypertension at 140/90 mm Hg and higher [1,5,7]. Mechanisms of increased blood pressure, leading to hypertension and/or strengthening of symptoms during pregnancy are very diverse.…”
Section: Introductionmentioning
confidence: 99%